Human Papillomavirus Deoxyribonucleic Acid Sequences and Clinical Outcomes of Cervical Cancer Patients Following Radiotherapy - Ching-Cheng Tseng; Chih-Jen Tseng; Chi-Chang Chang; Hung-Chih Hou; Chen-Bin Wang; Chun-Hung Chen (Elsevier, 2004)
Objective: To evaluate the status of human papillomavirus (HPV) following radiotherapy, and its prognostic significance in cervical cancer. Materials and Methods: Multiple tissue sections obtained from 58 patients with cervical cancer before and after radiotherapy were analyzed for the presence of HPV types 16 and 18 DNA by using the polymerase chain reaction. Results: The overall frequencies of HPV-16/18 infection among cervical cancer patients were 93.1% (54/58) and 56.9% (33/58) before and after radiotherapy, respectively. Patients with HPV-16 DNA-containing tumors were significantly associated with a favorable tumor response following radiotherapy compared with patients who had HPV-18-positive tumors (92.9% vs 50%, p = 0.002). After a median follow-up of 5.1 years (range, 3.2-6.5 years), patients with HPV-18-positive tumors were found to have a significantly higher relapse rate than HPV-16-positive patients (50.0% vs 14.3%, p = 0.02). Conclusion: The results suggest that cervical cancer patients with HPV-18 DNA in their tumors have a significantly poorer response to radiotherapy. This implies that the identification of HPV genotypes in cervical carcinoma may play a valuable role in predicting tumor response to radiotherapy.